Analisi e trasmissione di Messaggi di Allerta per la Gestione delle Emergenze Ambientali (GEOmedia, 2014)
Environmental Disaster Management requires quick respounce times and an efficient resources use. An efficient answer is necessary, thanks to Alerting messages integrated by accurate georeferenced event informations.The general scheme for rescue situation answer requires phenomenon knowledge, environmental monitoring, rapid Alerting services, quick intervention times and an optimumresources use.Police and emergencies management services need affordable knowledge of Disaster location, in order to efficiently coordinate rescue teams.This is particularly critic when traditional infrastructures are not operational due to the emergency conditions themselves (i.e.floodings, earthquakes, landslides, oils spilling, humanity intervention operations).In this paper a contribution to the prevention and management of environmental disasters, by the analysis of parameters relative to the identification and georeferencingof different tipologies of natural and anthropic disasters, is given.The strutture of CAP (Common AlertingProtocol) version 1.2, implemented byOasis, USA, giving the Alerting messagesstructure that can be sent simultaneously todifferent emergency management systems,simplyfing the operations requested to theteams involved into rescue operations, hasbeen herein analyzed.Alert Messages trasmission Systems havebeen also analyzed, included the possibilityto use EGNOS (European GeostationaryNavigation Overlay System) SIS (Signal InSpace).The final aim of this research is the extractionand real time visualization of georeferencedinformations on a mobile device(PDA, mobile phone).